SULFATION PATHWAYS: Steroid sulphatase inhibition via aryl sulphamates: clinical progress, mechanism and future prospects - Potter, B (BioScientifica, 2018)
Steroid sulphatase is an emerging drug target for the endocrine therapy of hormone-dependent diseases, catalysing oestrogen sulphate hydrolysis to oestrogen. Drug discovery, developing the core aryl O-sulphamate pharmacophore, has led to steroidal and non-steroidal drugs entering numerous clinical trials, with promising results in oncology and women’s health. Steroidal oestrogen sulphamate derivatives were the first irreversible active-site-directed inhibitors and one was developed clinically as an oral oestradiol pro-drug and for endometriosis applications. This review summarizes work leading to the therapeutic concept of sulphatase inhibition, clinical trials executed to date and new insights into the mechanism of inhibition of steroid sulphatase. To date, the non-steroidal sulphatase inhibitor Irosustat has been evaluated clinically in breast cancer, alone and in combination, in endometrial cancer and in prostate cancer. The versatile core pharmacophore both imbues attractive pharmaceutical properties and functions via three distinct mechanisms of action, as a pro-drug, an enzyme active-site-modifying motif, likely through direct sulphamoyl group transfer, and as a structural component augmenting activity, for example by enhancing interactions at the colchicine binding site of tubulin. Preliminary new structural data on the Pseudomonas aeruginosa arylsulphatase enzyme suggest two possible sulphamate-based adducts with the active site formylglycine as candidates for the inhibition end product via sulphamoyl or sulphonylamine transfer, and a speculative choice is suggested. The clinical status of sulphatase inhibition is surveyed and how it might develop in the future. Also discussed are dual-targeting approaches, development of 2-substituted steroidal sulphamates and non-steroidal derivatives as multi-targeting agents for hormone-independent tumours, with other emerging directions.